RT-UML IN MODELING OF MULTIMEDIA APPLICATIONS - Cichoń, Paweł (Computer Science, 2013)
RT-UML enables a structural and behavioral description of multimedia applications includingtime characteristic, however it does not offer mechanisms of a multimedia objects presentation(arrangement) expression or the time constrains expression between events. Thisfact illustrates RT-UML lack of expressive capabilities, especially in the context of multimediaapplications modeling. The presented in the paper extension of RT-UML illustrateshow multimedia objects arrangement and events synchronizations can be presented, whichmeans new type of diagrams addition to UML (presentation diagrams) and a synchronizedevents set class placing into the time model of RT-UML. Moreover extensions provide an applicationa graphical presentation of synchronized events to sequence and activity diagramsof UML, which enables time constrains of multimedia objects and their activities expression(synchronization of time events, which occur during presentation of multimedia objects).The originality of this approach relies on the extension of RT-UML syntax and on the presentationof an original method of multimedia applications modeling, which can make theproduction process more formalized and thus more precise.